Risk aided design of building structures - Woliński, Szczepan (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The potential failure of building structures usually arises from a combination of many unspecified causes or catastrophic events whose statistical description is highly uncertain and often impossible. Assumed or calculated reliability of the structure in a case is just a notional measure that can be used to compare the relative safety level of different structures in similar circumstances. Due to the difficulties associated with the estimation of the probability of different hazards as well as the assessment of consequences and costs of the structural damage and failure, also the risk analysis provides very uncertain information on the actual level of safety of a structure. The paper presents a proposal for an indirect approach to the probabilistic design of structures based not only on specific actions, but also on the ability of the structure to survive in the unique , unusual and vaguely defined circumstances. It requires a preliminary risk analysis before the standard procedures for shaping and dimensioning design elements will be applied.